Role of suppressor T cells in herpes simplex virus-induced immune deviation. - Whittum, J A (1984)
Herpes simplex virus type 1 inoculated into the anterior chamber of the mouse eye induces suppression of anti-herpes simplex virus T-cell-mediated delayed hypersensitivity. This suppression is virus-specific, and mediated by splenic T lymphocytes, and it can be adoptively transferred to naive recipients.